Life experiences vs digital inclusion: Factors influencing sense of security and their evolutions in China - Lijuan Zhao (PLoS ONE, 2025)
Background Digital technology is reshaping and enrich the types of social risks, making the lack of sense of security a widespread phenomenon. The predictors and enhancement strategies for the sense of security have drawn academic attention. However, there is still a debate on the relative effects of objective life experience and media construction on sense of security and how these influences evolve over time. Therefore, this study empirically examines the impact of digital media use and real-life experiences and their evolving mechanisms. Methods This study based on data from CSS in 2013, 2017, and 2021, explored the impact and evolution of life experiences and digital inclusion on sense of security from the perspectives of experiential shaping and media construction. Results Results indicate that negative life experiences have a significant negative impact on sense of security, which first decreases but then increases over time. Digital inclusion also has a significant negative impact on sense of security, and this trend diminishes over time. Moreover, the results of relative importance show that despite digital inclusion’s growing explanatory power, life experiences remain dominant, which means the current level of digital inclusion still cannot shake the decisive role of personal experiences. The educational differences in the impact of digital inclusion on sense of security suggest that education and digital literacy can mitigate the negative effects of digital inclusion, potentially turning them into positive influences. Conclusion The findings indicate that in the process of digital society risk governance, it is also necessary to closely monitor the real-life domains of the public in order to achieve risk governance in both online and offline spaces.